Inactivation of the inhA-Encoded Fatty Acid Synthase II (FASII) Enoyl-Acyl Carrier Protein Reductase Induces Accumulation of the FASI End Products and Cell Lysis of Mycobacterium smegmatis - Vilchèze, Catherine (American Society for Microbiology, 2000)
The mechanism of action of isoniazid (INH), a first-line antituberculosis drug, is complex, as mutations in at least five different genes (katG, inhA, ahpC, kasA, and ndh) have been found to correlate with isoniazid resistance. Despite this complexity, a preponderance of evidence implicates inhA, which codes for an enoyl-acyl carrier protein reductase of the fatty acid synthase II (FASII), as the primary target of INH. However, INH treatment of Mycobacterium tuberculosis causes the accumulation of hexacosanoic acid (C(26:0)), a result unexpected for the blocking of an enoyl-reductase. To test whether inactivation of InhA is identical to INH treatment of mycobacteria, we isolated a temperature-sensitive mutation in the inhA gene of Mycobacterium smegmatis that rendered InhA inactive at 42°C. Thermal inactivation of InhA in M. smegmatis resulted in the inhibition of mycolic acid biosynthesis, a decrease in hexadecanoic acid (C(16:0)) and a concomitant increase of tetracosanoic acid (C(24:0)) in a manner equivalent to that seen in INH-treated cells. Similarly, INH treatment of Mycobacterium bovis BCG caused an inhibition of mycolic acid biosynthesis, a decrease in C(16:0), and a concomitant accumulation of C(26:0). Moreover, the InhA-inactivated cells, like INH-treated cells, underwent a drastic morphological change, leading to cell lysis. These data show that InhA inactivation, alone, is sufficient to induce the accumulation of saturated fatty acids, cell wall alterations, and cell lysis and are consistent with InhA being a primary target of INH.